Influence of sowing dates and weather factors on development of Alternaria blight on rapeseed-mustard - and S.J. KOLTE, RUCHI GUPTA, R.P. AWASTHI (Indian Phytopathology, 2003)
The crop sown on 21st October recorded significantly less disease severity, which was enhanced in subsequent sowing dates. Cultivar PT 303 showed significantly more disease severity followed by Divya and Kranti on all the sowing dates. Eighty five-day old plants showed highest disease severity because temperature [maximum (20.4-31.6Â°C) and minimum (4.9-14.4Â°C)] had significant negative correlation, while relative humidity [maximum (80-94%) and minimum (33-56%)] had significant positive correlation with disease severity. Prediction equations were fitted for forecasting of the disease at different growth stages of the crop.